PWE-140 Validation of the 'failure to provide adequate relief' (F-par) scale in a specialist clinic setting. (8th June 2018) - Mari, Amir; Zarate-Lopez, Natalia; Chatoor, Dave; Passananti, Valentina; Emmanuel, Anton
Abstract : Background: Treatment of chronic idiopathic constipation is empiric, based on step-wise approach. If first-line conservative treatment (lifestyle and laxatives) do not relieve symptoms, secondary approaches with prokinetic or secretagogue drugs are used before considering hospital-based care (biofeedback, psychosocial support, transanal irrigation (TAI), surgery). Nevertheless, patients are often unsatisfied with care and fail to progress to adequate levels of therapy. The 5-point Failure to Provide Adequate Relief (F-PAR) scale was developed to facilitate the recognition of when to move from one step to the next. The aim of this study was to validate F-PAR in a tertiary clinic setting. Methods: We studied 403 consultations of 331 patients (262 women, mean age 41) . All fulfilled Rome III/IV diagnostic criteria for chronic constipation. Immediately prior to clinical assessment by one of 2 experienced physicians, participants completed the F-PAR scale; patients were seen blind to the F-PAR result.Consultant clinic assessment was undertaken to identify efficacy of the current management as the gold standard. Results: Table 1 shows detail of the 403 consultations, in 200 of which clinical assessment identified inadequate relief with current therapy. Neither duration nor types of treatment were correlated with relief. All individual items of the F-PAR had Specificity >96% but poor sensitivity (15%–67%).Cumulatively, none of the subjects with ≥4 positive responses had adequate relief. By contrast, there was excellent sensitivity and specificity for patients with no positive F-PAR replies. Conclusion: The F-PAR has excellent specificity, suggesting it is a useful confirmatory test to confirm a clinical suspicion of inadequate relief. Good sensitivity is only seen if there are no positive FPAR replies, implying the F-PAR is only of screening value when there is high likelihood of treatment satisfaction. As such, the F-PAR may have a role in confirming efficacy of treatments in trials of therapy for chronic constipation.